The videoclip as an extension of music: Points for analysis - Janotti Junior, Jeder Silveira (2007)
The videoclip as an extension of music: Points for analysis — This article scrutinizes the mediatic analysis methodology of the shift of popular songs towards the videoclip. Our starting point is an analysis of the bonds linking music to videoclips, discussing the ideas of passage, chorus and diction of the song in the field of videoclip imagery based on concepts of Semiotics and on Cultural Studies. The concepts of musical genres underpin our debate on this audiovisual instrument, extending it beyond a textual analysis to understand its dynamics of consumption. Through the idea of the performance of mass pop music, we discuss concepts that help us outline categories that can be applied in a future methodology of mediatic videoclip analysis.